Strategies to model scheduling decisions to plan the soft drink production process - Rangel, Socorro; Maldonado, Michelli [UNESP] (My University, 2012)
In this paper we present a mixed integer model that integrates lot sizing and lot scheduling decisions for the production planning of a soft drink company. The main contribution of the paper is to present a model that differ from others in the literature for the constraints related to the scheduling decisions. The proposed strategy is compared to other strategies presented in the literature.
Keywords: Asymmetric traveling salesman problem; Integrated lot sizing and scheduling models; Production planning; Lot sizing; Lot-scheduling; Mixed integer models; Production Planning; Production process; Scheduling decisions; Scheduling models; Soft drink companies; Soft drinks; Beverages; Planning; Production control; Production engineering; Scheduling